“To Convince to defeat”: The aerial bombardments of civil population in 1938 and the diplomatical offensive of the Republican Spanish Government in France and United Kingdom - Payá López, Pedro (Hispania Nova, 2021)
This paper offers a global interpretation of the role that aerial bombardments of open cities played in the diplomatic strategy that the Spanish Republic deployed in France and United Kingdom in 1938. It studies some little-known aspects about the creation of the Commission for the investigation of air bombardments in June and August of that year, and the pressure exerted on the League of Nations in the aftermath of the Spanish Civil War. This episode shows that the outcome of the Spanish conflict depended on its internationalization and proves the effects of the isolation of Spanish Republic. The sources used to elaborate this paper are mainly diplomatic.